2020
DOI: 10.31486/toj.19.0057
|View full text |Cite
|
Sign up to set email alerts
|

The Modified Early Warning Score as a Predictive Tool During Unplanned Surgical Intensive Care Unit Admission

Abstract: Background: The Modified Early Warning Score (MEWS) has been proposed to warn healthcare providers of potentially serious adverse events. We evaluated this scoring system during unplanned escalation of care in hospitalized surgical patients during a 1-year period. Methods: Following institutional review board approval, all consecutive, unplanned surgical admissions into the surgical intensive care unit (SICU) during 2016 were entered into this study. MEWS and patient demographics during bedside evaluation for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
(61 reference statements)
0
7
0
1
Order By: Relevance
“…Many observational studies, as well as pre-intervention and post-intervention evaluation analyses indicating EWS systems, have improved the detection of deterioration clinically [ 20 , 21 ]. Previous studies have shown that MEWS might be useful in reducing mortality in hospital patients [ 22 ]. Thus Modified Early Warning Score (MEWS) will be a protocol to identify patients in hospitals who are at risk of unexpected deterioration catastrophically [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many observational studies, as well as pre-intervention and post-intervention evaluation analyses indicating EWS systems, have improved the detection of deterioration clinically [ 20 , 21 ]. Previous studies have shown that MEWS might be useful in reducing mortality in hospital patients [ 22 ]. Thus Modified Early Warning Score (MEWS) will be a protocol to identify patients in hospitals who are at risk of unexpected deterioration catastrophically [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brazilian Journal of Development, Curitiba, v.7, n.11, p. 106335-106341 nov. 2021 Pontuações baixas na escala (<2), relacionaram-se significativamente com menor probabilidade de eventos graves (MONTENEGRO; MIRANDA, 2019) e necessidade de intervenção imediata. Apesar da extrapolação da escala ser relativamente comum, ela não é melhor, por exemplo, que a qSOFA (quick SOFA) para pacientes sépticos (KHWANNIMIT; BHURAYANONTACHAI; VATTANAVANIT, 2019; KRAMER; SEBAT; LISSAUER, 2019), e há controvérsia sobre ser universalmente aplicável como preditora de admissão em UTI de pacientes cirúrgicos não-eletivos (KUMAR et al, 2020). Do mesmo modo, em um estudo retrospectivo e observacional, obteve-se relação significativa da pontuação na escala MEWS (>6, AUC 0,82) do momento da alta até as 48 horas seguintes, e maior probabilidade de readmissão na UTI (BALSHI et al, 2020).…”
Section: Discussionunclassified
“…As more people have access to road transportation, road traffic accidents have increased, and trauma has become a major problem in emergency medical rescue. The Modified Early Warning Score (MEWS) system has been widely used in many countries because it is quick, easy, and practical (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Scores are based on 5 items of body temperature, heart rate, consciousness, systolic blood pressure, and respiration.…”
Section: Introductionmentioning
confidence: 99%